High-strength filling aggregate prepared based on inferior tailings as well as preparation method and application of high-strength filling aggregate
Through the granular compression and dense reconstruction treatment of inferior tailings sand and the mixing with cementing slurry, the problems of low density and strength of inferior tailings sand are solved, the density and strength of the filling body are improved, and the consumption of tailings sand is increased. , reduces the cost of gelling materials and achieves the goal of tailings-free mines.
Patent Information
- Application Number
- CN202411637097.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
Due to the characteristics of ultra-fine particle size and high moisture content, the filling slurry prepared by conventional cementing and filling technology has poor density and low strength, and gelling materials need to be added to improve strength, resulting in a decrease in the consumption of inferior tailings. The purpose of tailings-free mines cannot be effectively achieved.
Through the granular compression and dense reconstruction treatment of inferior tailings sand, high-strength filling aggregate is prepared, and mixed evenly with the cementing slurry to prepare it into a cementing filling slurry, which is self-flow or pumped to the area to be filled, improving the density of the filling body and Strength, increase the consumption of inferior tailings sand.
It realizes that while ensuring strength requirements and conveying performance, improves the compactness of the filling body, increases the consumption of inferior tailings, reduces the operating costs of gelled materials, simplifies the process flow, avoids high-temperature sintering and high-energy-consuming processes, and is equipped with Strong implementability.
Smart Images

Figure CN119285263A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of mine filling, and in particular to a high-strength filling aggregate prepared based on inferior tailings, a preparation method and an application thereof. Background Art
[0002] Due to the ultra-fine particle size and high mud content of low-quality tailings, the filling slurry prepared by conventional cementing filling process has the characteristics of complex process, low filling concentration, high water content, etc. After filling into the underground, the filling body formed has poor density, low strength, and slow strength formation. In addition, when low-quality tailings are used to prepare filling slurry by conventional cementing filling process, cementitious materials need to be added to achieve the purpose of improving strength, resulting in a corresponding decrease in the proportion of low-quality tailings contained in the unit volume of the filling slurry, and the capacity of the underground goaf is limited, so the amount of low-quality tailings that can be absorbed is also less than that of conventional tailings, and the purpose of tailings-free mine cannot be effectively achieved. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.
[0004] On the one hand, the present application proposes a method for preparing high-strength filling aggregate based on inferior tailings, in which inferior tailings are granulated, compressed, densified and reconstructed to form high-strength filling aggregate. The process flow is relatively simple and does not require high-temperature sintering, preparation of dry powder, large air volume dust collection and other high-energy-consuming processes, and has strong feasibility.
[0005] On the other hand, the present application proposes a high-strength filling aggregate prepared based on inferior tailings. The high-strength filling aggregate formed by the preparation method provided by the present application has transportability while ensuring strength requirements.
[0006] On the other hand, the present application proposes an application of high-strength filling aggregate prepared based on inferior tailings, wherein the high-strength filling aggregate provided in the present application is mixed with a cementing slurry by stirring and evenly mixing to form a cementing filling slurry, and the cementing filling slurry is transported to the area to be filled by gravity or pumping to improve the density and strength of the filling body, and also increase the consumption of inferior tailings.
[0007] According to an embodiment of the first aspect of the present application, a method for preparing high-strength filling aggregate based on inferior tailings is proposed, comprising the following steps:
[0008] The inferior tailings are filtered and further dehydrated to form a tailings filter cake with a moisture content of 10%-15%;
[0009] 90%-100% of the tailings filter cake and 0%-10% of the binder are mixed and compressed to form tailings particles with a diameter of D1, wherein D1 is less than or equal to 5 mm.
[0010] The tailings particles are cooled and solidified and air-dried to obtain filling aggregates with a moisture content of 5% to 15%.
[0011] In some embodiments, the particle size of the inferior tailings is D2; wherein D2≤0.075 mm;
[0012] And / or, the inferior tailings are filtered to form a filter cake having a moisture content of 15% to 25% and then dehydrated;
[0013] And / or, the filter cake having a moisture content of 15%-25% is naturally dehydrated.
[0014] In some embodiments, the density of the tailings particles is ρ1, and the density of the inferior tailings is ρ2; wherein ρ1≥1.1×ρ2.
[0015] In some embodiments, the tailings particles are left to stand in an open field for natural cooling and natural air drying.
[0016] Among them, after the difficult-to-handle inferior tailings are granulated, compressed and densified, their mechanical properties are greatly improved, their density is increased, and their strength is improved to achieve their application as filling coarse aggregate. Through the compression and densification of inferior tailings, the density of the filling body can be effectively improved when it is used while ensuring the strength requirements and transportation performance, thereby effectively increasing the consumption of inferior tailings. In addition, the process flow of this application is relatively simple, and does not require high-energy-consuming processes such as high-temperature sintering and preparation of dry powder, and has strong feasibility.
[0017] According to an embodiment of the second aspect of the present application, a high-strength filling aggregate prepared based on inferior tailings is proposed, which is prepared by the method described in any of the above embodiments, and inferior tailings with a particle size of D2 are made into filling aggregate; wherein D2≤0.075mm.
[0018] In some embodiments, the density of the filling aggregate is ρ, and the density of the inferior tailings is ρ; wherein ρ≥1.1×ρ2.
[0019] The filling aggregate provided in the present application is prepared by using inferior tailings, and has transportability while ensuring strength requirements.
[0020] According to an embodiment of the third aspect of the present application, it is proposed that the filling aggregate described in any of the above embodiments is used in filling mine goafs. The filling aggregate is mixed with a binder slurry as a coarse aggregate at a set ratio to form a binder filling slurry for filling mine goafs.
[0021] In some embodiments, the mass concentration of the cementitious slurry is 55%-70%;
[0022] and / or, in terms of percentage by mass, the cementitious slurry comprises 75%-100% of fine aggregate and 0%-25% of cementitious material;
[0023] and / or, the stirring speed for forming the cementing slurry is greater than or equal to 80 r / min;
[0024] And / or, the fine aggregate is low-quality tailings with a particle size of D2, wherein D2≤0.075 mm.
[0025] In some embodiments, the filling aggregate and the cementitious slurry are mixed under a stirring condition of less than or equal to 60 r / min.
[0026] In some embodiments, the mass concentration of the cementitious filling slurry is 60%-75%;
[0027] And / or, in terms of mass percentage, the cementitious filling slurry includes 8%-40% of the filling aggregate, 60%-92% of the fine aggregate and 0%-23% of the cementitious material.
[0028] In the present application, high-strength filling aggregate is used as coarse aggregate, which is evenly mixed with cementing slurry by stirring to prepare green and pollution-free cementing filling slurry, which can effectively improve the quality of cementing filling slurry prepared with inferior tailings as the main raw material and reduce the amount of cementitious material added, effectively reduce the proportion of operating costs of cementitious materials and improve the density of the filling body when filling the mine goaf, increase the consumption of inferior tailings and effectively achieve the goal of tailings-free mines.
[0029] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0031] Figure 1 It is a flow chart of a method for preparing a cementitious filling slurry provided in one embodiment of the present application. DETAILED DESCRIPTION
[0032] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.
[0033] The conventional tailings cementing filling process includes selecting low-concentration tailings and transporting them to the tailings concentration equipment of the filling station. After flocculation, sedimentation and concentration, the high-concentration tailings slurry is mixed with water and cementitious materials (such as cement, etc.) in a certain proportion to prepare a uniform cementing filling slurry, which is transported to the goaf waiting for filling through pipelines. The cementing slurry undergoes a period of dehydration and hydration reaction to form a filling body with a certain strength. Due to the ultra-fine particle size, high water content and mud content of inferior tailings, the filling slurry prepared by the conventional cementing filling process has the characteristics of low filling concentration and high water content. When it is filled into the well, it has the disadvantages of poor density, low strength and slow strength formation. On the other hand, due to the high water content and fine particle size of the filling slurry, it is usually necessary to increase the amount of cementitious material added to achieve the purpose of improving strength, resulting in a corresponding decrease in the proportion of tailings contained in the unit volume of the filling body. However, the underground goaf is limited, and the amount of inferior tailings that can be absorbed by the filling is also less.
[0034] Tailings (or tailings) are waste discharged by the ore dressing plant after grinding the ore and selecting the useful components under specific economic and technical conditions. Inferior tailings are tailings with finer particle size, graded fine tailings, and tailings with poor chemical composition, that is, tailings that are difficult to cement to form strength. High-quality tailings or the coarser part of tailings can usually be used as the main material to fill the goaf, or as building materials and other effective comprehensive utilization, while the remaining tailings with extremely fine particle size (generally refers to less than 0.075mm) have the characteristics of ultra-fine fineness, high water content and mud content. When it can be used as a filling material, it can effectively realize a tailings-free mine. When the inferior tailings with high water content and mud content are concentrated (dewatered) in the conventional way, its density does not change much.
[0035] However, the prepared slurry has poor quality, low filling strength, poor durability, and is difficult to be effectively utilized in other ways. In addition, some tailings are difficult to be comprehensively utilized due to chemical composition and other reasons, and are usually not very good filling materials. It is difficult to prepare qualified filling materials with expected strength at low cost.
[0036] Therefore, the density of the tailings filling body is poor, resulting in that most of the tailings produced by the mine cannot be fully filled and need to be stored on the surface to form a tailings pond. Since there is no effective and feasible method to compress the tailings after filling the mining area to make the filling body denser, the current main technical direction for eliminating surface tailings is conventional filling and comprehensive utilization of tailings. However, the comprehensive utilization of tailings is limited by the scope of product supply, and it is difficult to fundamentally consume tailings on a large scale.
[0037] Related technologies provide methods for the treatment of ultrafine tailings for filling processes, such as placing ultrafine tailings and cement powder in a certain proportion into a mining granulator disc to form balls, spraying the disc surface with mixed dry materials through a spray system to form spherical particles to obtain tailings balls; then using the tailings balls, ultrafine tailings, cement powder and water to be uniformly stirred through a stirring system, and then transported to the goaf through a filling system. Some related technologies also disclose using a dehydration device (including a tailings concentration device and a filter press) to dehydrate the tailings slurry containing tailings to form dehydrated tailings, the dehydrated tailings and a binder are mixed to form tailings granulation raw materials, and the tailings are made into tailings particles after adding water through a disc granulator, and then mixed with tailings slurry and cementitious materials to prepare a cementitious filling slurry for filling.
[0038] Among them, the relevant technologies mainly use disc granulators, and the prepared particles are relatively loose. As aggregates, they have poor effects in improving filling quality and cannot fundamentally improve filling quality; in addition, they cannot increase the consumption of tailings. At the same time, in the relevant technologies, the tailings must be concentrated, filtered, dried or naturally dried, crushed to prepare dry powder, and then added with gelling materials and sprayed with water. The tailings are prepared into tailings particles by a disc granulator, and then prepared into filling slurry through conventional belt conveying, stirring and mixing with tailings slurry. Especially in the process of preparing dry powder after tailings filtration, a large amount of space is required and crushing, dust collection and other facilities are configured, resulting in the overall process being too complicated and the floor space increased. Among them, additional crushing, dust collection, belt reverse transportation and other equipment are also configured, resulting in increased investment, increased energy consumption, and high operating costs.
[0039] Some solutions also mention that 85-90wt% of ultrafine tailings, 5-10wt% of quicklime, and 0-5wt% of fly ash are mixed in a certain proportion, and then water is added to the mixture to granulate to obtain raw balls, and the raw balls are calcined at 800-1000°C for 20-60 minutes, and coarse aggregate is obtained after cooling. And some related technologies also disclose that 85-90wt% of ultrafine tailings, 5-10wt% of quicklime, and 0-5wt% of fly ash are mixed in a certain proportion, and then water is added to the mixture to granulate to obtain 5-10mm raw balls, and after steam curing and full solidification, granular coarse aggregate is obtained. Among them, the related technologies require calcining or steam curing of the raw balls, which have the disadvantages of complex process, large investment, high energy consumption, and high cost.
[0040] Based on this, the technical solution of the embodiment of the present application provides a high-strength filling aggregate prepared from inferior tailings, a preparation method and an application, and uses inferior tailings to form high-strength filling aggregates by granulating, compressing and densifying them. The process flow is relatively simple, and high-energy-consuming processes such as high-temperature sintering, preparing dry powder, and collecting dust with large air volume are not required, so it has strong feasibility. In addition, the high-strength filling aggregate provided in the present application is mixed with the cementing slurry by stirring and evenly mixing to prepare a cementing filling slurry, and the cementing filling slurry is transported to the area to be filled by gravity or pumping to improve the density and strength of the filling body, and also increase the consumption of inferior tailings.
[0041] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0042] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0043] To achieve the above object, according to an embodiment of the first aspect of the present application, a method for preparing high-strength filling aggregate based on inferior tailings is proposed, comprising the following steps:
[0044] S1: The inferior tailings are filtered and further dehydrated to form a tailings filter cake with a moisture content of 10%-15%;
[0045] S2: 90%-100% of tailings filter cake and 0%-10% of binder are mixed and compressed to form tailings particles with a diameter of D1, wherein D1≤5mm;
[0046] S3: The tailings particles are cooled and air-dried to obtain filling aggregates with a moisture content of 5%-15%.
[0047] In S1, the inferior tailings with a density of ρ2 and a particle size of D2 are filtered through a filter press to form a filter cake with a moisture content of 15%-25%, and then placed in a stockpile for natural dehydration to form a tailings filter cake with a moisture content of 10%-15%; wherein D2≤0.075mm. The inferior tailings are first filtered through a filter press to quickly dehydrate them and then naturally dehydrated to form a tailings filter cake with a moisture content of 10%-15%, for example, the moisture content of the tailings filter cake is 10%, 11%, 12%, 13%, 14% or 15%, etc., wherein the moisture content refers to the ratio of the water content in the material to the total weight of the material.
[0048] In S2, the tailings filter cake and the binder are transported to a dry sand mixer and mixed, and then compressed and granulated by a compression granulator to obtain tailings particles, wherein the density of the tailings particles is ρ1 and the diameter is D1; wherein ρ1≥1.1×ρ2; further, ρ1=(1.1-1.3)×ρ2, D1≤5mm.
[0049] Wherein, in terms of mass percentage, the mass percentage of the tailings filter cake is 90%-100%, and the mass percentage of the binder is 0%-10%. For example, the mass percentage of the tailings filter cake is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.; if the content of the tailings filter cake is lower than 90%, the utilization rate of the inferior tailings is low, and the redundant amount of inferior tailings cannot be effectively absorbed. In the present application, for example, the binder can be exemplified by fly ash, cement, cement powder, etc., and its mass percentage is 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, etc.
[0050] In S3, the tailings particles are placed in an open field for 2 hours for cooling and solidification, and then naturally air-dried to obtain filling aggregates with a moisture content of 5%-15%. The moisture content of the filling aggregates is 5%, 6%, 7%, 8%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0051] Among them, after the difficult-to-handle inferior tailings are granulated, compressed and densified, their mechanical properties are greatly improved, their density is increased, and their strength is improved to achieve their application as filling coarse aggregate. Through the compression and densification of inferior tailings, the density of the filling body can be effectively improved when it is used while ensuring the strength requirements and transportation performance, thereby effectively increasing the consumption of inferior tailings. In addition, the process flow of this application is relatively simple, and does not require high-energy-consuming processes such as high-temperature sintering and preparation of dry powder, and has strong feasibility.
[0052] According to the embodiment of the second aspect of the present application, a high-strength filling aggregate prepared based on inferior tailings is proposed, which is prepared by the method in any of the above embodiments, and inferior tailings with a particle size of D2 are made into filling aggregate; wherein D2≤0.075mm; the density of the filling aggregate is ρ, and the density of the inferior tailings is ρ2; wherein ρ≥1.1×ρ2; further, ρ1=(1.1-1.3)×ρ2. The filling aggregate provided by the present application is prepared using inferior tailings, and has transportability while ensuring strength requirements.
[0053] According to an embodiment of the third aspect of the present application, it is proposed that the filling aggregate in any of the above embodiments is used in filling mine goafs, and the filling aggregate is mixed with a binder slurry as a coarse aggregate at a set ratio to form a binder filling slurry for filling mine goafs.
[0054] The mass concentration of the cementitious slurry is 55%-70%; in terms of mass percentage, the cementitious slurry includes 75%-100% fine aggregate and 0%-25% cementitious material, wherein the fine aggregate is inferior tailings with a particle size of D2, wherein D2≤0.075mm.
[0055] For example, using inferior tailings with a particle size of less than or equal to 0.075mm as fine aggregate, and taking cementing slurry as the basis, fine aggregate with a mass percentage of 75%-100% and cementing material with a mass percentage of 0%-25% and a certain amount of water are mixed and uniformly prepared into cementing slurry through a high-speed stirring, and the stirring speed is greater than or equal to 80r / min. For example, the mass percentage of fine aggregate is 75%, 80%, 85%, 90%, 95%, 100%, etc., and the mass percentage of cementing material is 0%, 5%, 10%, 15%, 20%, 25%, etc. When the mass percentage of cementing material is high, such as higher than 25%, the unit filling cost is high.
[0056] In the application process, for the convenience of preparation, inferior tailings with a particle size of less than or equal to 0.075 mm can be used as fine aggregate to first make tailings slurry, and the tailings slurry is mixed with a cementitious material, wherein the cementitious material can be exemplified by cement and the like.
[0057] In some embodiments, filling aggregate is quantitatively added to the cementitious slurry and mixed with the cementitious slurry; the filling aggregate and the cementitious slurry are mixed under stirring conditions of less than or equal to 60r / min to form a cementitious filling slurry with a mass concentration of 60%-75%; in terms of mass percentage, the cementitious filling slurry includes 8%-40% filling aggregate, 60%-92% fine aggregate and 0%-23% cementitious material.
[0058] Among them, the filling aggregate is quantitatively added to the cementing slurry according to a preset ratio through a quantitative conveyor, and is evenly mixed at a low speed in a mixer, and the stirring speed is ≤60r / min, to form a cementing filling slurry with a mass concentration of 60%-75%. The mass concentration of the cementing filling slurry is 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 60%, 71%, 72%, 73%, 74%, 75%, etc. In this application, high-strength filling aggregate is used as coarse aggregate, and is quantitatively added to the cementing slurry according to a preset ratio. It is evenly mixed with the cementing slurry at a low stirring speed, so that the filling aggregate is not easily broken up by high-speed stirring.
[0059] Among them, based on the cementitious filling slurry, the cementitious filling slurry includes 8%-40% filling aggregate, 60%-92% fine aggregate and 0%-23% cementitious material in terms of mass percentage. For example, the mass percentage of filling aggregate is 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc. Too much filling aggregate content will affect the fluidity of the cementitious filling slurry, and too low filling aggregate content will not effectively absorb more inferior tailings; the mass percentage of fine aggregate is 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, etc.; the mass percentage of cementitious material is 0%, 5%, 10%, 15%, 20%, 23%, etc. In some solutions, the mass concentration of the cementitious filling slurry is 69.5%, which includes 73.5% fine aggregate, 18.4% filling aggregate and 8.1% cementitious material in terms of mass percentage.
[0060] In the related art, the cost of cementitious materials usually accounts for more than half of the filling cost. When inferior tailings are used alone as filling materials, more cementitious materials need to be added to ensure the filling strength, but the cost is that the filling operation cost is greatly increased. The coarse-grained aggregate prepared by the inferior tailings through granulation, compression, densification and reprocessing in this application can reduce the amount of cementitious materials added while ensuring the filling strength, and effectively reduce the proportion of cementitious materials operating costs.
[0061] In summary, this application compresses and cements part or all of the filling materials of inferior tailings to form a denser and higher-strength filling aggregate, and uses it as a kind of coarse aggregate filling material, and then reasonably proportions it with the cementing slurry formed by fine aggregate and cementitious material to form a cemented filling slurry, which has good pipeline transportation performance and can effectively increase the filling concentration and reduce the water content, thereby improving the density of the filling body and increasing the consumption of filling tailings. This application can not only ensure the safety of underground mining, but also maximize the low-cost consumption of inferior tailings and reduce the surface stockpile of inferior tailings. By granulating, compressing, and densifying the inferior and difficult-to-handle inferior tailings and then reprocessing them, the filling preparation process using them as aggregate can effectively improve the density of the filling body, reduce the proportion of cementitious materials and water per unit volume of filling weight, and increase the proportion of inferior tailings, while ensuring the strength requirements and transportation performance. , And then effectively increase the consumption of inferior tailings.
[0062] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.
[0063] Example 1
[0064] This embodiment provides a high-strength filling aggregate prepared based on inferior tailings, and its preparation method and specific operating parameters are as follows: 3 The inferior tailings with a particle size of 0.075 mm are filtered to form a filter cake with a moisture content of 15%, which is then placed in a storage yard for natural dehydration to form a tailings filter cake with a moisture content of 13%; the tailings filter cake and the binder are transported to a dry sand mixer and mixed, and then compressed and granulated by a compression granulator to obtain a density of 2.152t / m 3 The tailings particles with a diameter of 5 mm were placed in an open field for 2 hours to cool and solidify, and then naturally dried to obtain filling aggregate with a moisture content of 5%.
[0065] Inferior tailings with a particle size of 0.075 mm are used as fine aggregate, which is mixed with cementitious material in water at a stirring speed of 80 r / min to prepare a cementitious slurry with a mass concentration of 58.6%. The filling aggregate with a moisture content of 5% obtained above is mixed with the cementitious slurry at a stirring speed of 60 r / min at a delivery flow rate of 30 t / h to obtain a cementitious filling slurry with a mass concentration of 64.7%, wherein the cementitious filling slurry includes 29% filling aggregate, 61% fine aggregate and 10% cementitious material.
[0066] The proportion of filling aggregate, the proportion of fine aggregate, the proportion of cementitious material, the mass concentration of filling slurry, the stirring speed for forming cementitious slurry (first stage stirring speed) and the stirring speed for forming cementitious filling slurry (second stage stirring speed) are adjusted according to Table 1 to prepare cementitious filling slurries in different embodiments and comparative examples. The cementitious filling slurries prepared in the above-mentioned embodiments and comparative examples are subjected to performance testing, and the results are shown in Table 2.
[0067] Table 1 Test results of cementing filling slurry in various embodiments and comparative examples
[0068]
[0069] Table 2 Test results of cementing filling slurry in various embodiments and comparative examples
[0070]
[0071]
[0072] According to the above results, it can be seen that under the same amount of cement addition, the uniaxial compressive strength of the filling slurry prepared by the technical solution of the present application is significantly improved at 3 days, 7 days and 28 days, and the density of the filling slurry is improved. Among them, the 3-day strength value in Comparative Examples 1-5 cannot be measured, and the compression granulation process adopted in this application is to solve this problem. When the conventional technical solution is adopted to achieve the same filling strength as the technical solution of the present application, the proportion of cementitious materials must be increased, and the corresponding amount of inferior tailings that can be filled into the well is reduced. Therefore, the technical solution of the present application can improve the density and strength of the filling body, and also increase the consumption of inferior tailings. Among them: the greater the slump, the better the fluidity.
[0073] According to the above results, it can be seen that under the same ratio and the same total stirring time, the filling slurry prepared by the technical solution of the present application (two-stage stirring) has significantly improved fluidity compared with the conventional method (one-stage high-speed stirring), which is conducive to pipeline transportation.
[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0075] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing high-strength filling aggregate based on inferior tailings, characterized in that: The following steps are involved: The inferior tailings are filtered and further dehydrated to form a tailings filter cake with a moisture content of 10%-15%; 90%-100% of the tailings filter cake and 0%-10% of the binder are mixed and compressed to form tailings particles with a diameter of D1, wherein D1 is less than or equal to 5 mm. The tailings particles are cooled and solidified and air-dried to obtain filling aggregates with a moisture content of 5% to 15%.
2. The method according to claim 1, characterized in that The particle size of the inferior tailings is D2; wherein D2≤0.075mm; And / or, the inferior tailings are filtered to form a filter cake having a moisture content of 15% to 25% and then dehydrated; And / or, the filter cake having a moisture content of 15%-25% is naturally dehydrated.
3. The method according to claim 1, characterized in that The density of the tailings particles is ρ1, and the density of the inferior tailings is ρ2; wherein ρ1≥1.1×ρ2.
4. The method according to any one of claims 1 to 3, characterized in that: The tailings particles are left to stand in an open area for natural cooling and natural air drying.
5. A high-strength filling aggregate prepared based on inferior tailings, characterized in that: Using the method described in any one of claims 1 to 4, inferior tailings with a particle size of D2 are made into filling aggregate; wherein D2≤0.075mm.
6. The filling aggregate according to claim 5, characterized in that: The density of the filling aggregate is ρ, and the density of the inferior tailings is ρ2; wherein ρ≥1.1×ρ2.
7. The filling aggregate according to claim 5 or 6 is used in filling the goaf of a mine, characterized in that: The filling aggregate is used as coarse aggregate and is mixed with a cementing slurry at a set ratio to form a cementing filling slurry for filling the goaf of a mine.
8. The use according to claim 7, characterized in that: The mass concentration of the cementing slurry is 55%-70%; and / or, in terms of percentage by mass, the cementitious slurry comprises 75%-100% of fine aggregate and 0%-25% of cementitious material; and / or, the stirring speed for forming the cementing slurry is greater than or equal to 80 r / min; And / or, the fine aggregate is low-quality tailings with a particle size of D2, wherein D2≤0.075 mm.
9. The use according to claim 7, characterized in that: The filling aggregate and the cementitious slurry are mixed under a stirring condition of less than or equal to 60 r / min.
10. The use according to claim 8, characterized in that: The mass concentration of the cementing filling slurry is 60%-75%; And / or, in terms of mass percentage, the cementitious filling slurry includes 8%-40% of the filling aggregate, 60%-92% of the fine aggregate and 0%-23% of the cementitious material.
Citation Information
Patent Citations
Preparation process for preparing recycled aggregate based on tailings and aggregate
CN112777957A
Tailing sand filling treatment method
CN117868976A